Cognitive function of young male tennis players and non-athletes - Petra Pačesová; Pavel Šmela; Stanislav Kraček; Klaudia Kukurová; Lucia Plevková (Palacký University Olomouc, 2018)
Background: Cognitive functions can be defined as the ability of individuals to participate, recognize and plan responses to external and internal impulses. We can define attention as the active focus of our consciousness and the ability to concentrate mental functions on a certain activity. In competitive tennis, attention, especially conscious attention which is controlled by cognitive and volitional processes plays a significant role. Objective: The aim of this study was to assess differences in cognitive functions between tennis players and non-athletic adolescents. Methods: The research sample consisted of 98 subjects: 44 tennis players (age 18.11 ± 1.35 years) and 54 nonathletic adolescents (age 18.04 ± 1.33 years). The level of cognitive functions was investigated using the standardized neuropsychological cognitive Stroop test. Results: The tennis players had higher cognitive function scores compared to the non-athletes in two of the three segments of the Stroop test. There was no significant difference between the groups in the simplest segment of the Stroop test (segment T). However, a significant difference (p = .028; d = 0.45) was found between the tennis players and non-athletes in segment S of the Stroop test and in segment B, the most difficult segment of the test, the difference between research groups was also significant (p = .002; d = 0.63). Conclusion: Based on acquired data, we can see a difference between athletes and non-athletes in cognitive functions such as cognition inhibitory control, concentration of attention, conscious and selective attention. However, the differences have only been demonstrated in moderate difficulty and most difficulty segment, in the simplest segment we have not found difference between athletes and non-athletes.